Higher Education Reforms in Romania: Between the Bologna Process and National Challenges - Curaj, A (Springer, 2016)
Romania is an active player in various international higher education areas, while undergoing a series of higher education reforms within its national framework. The Higher Education Evidence Based Policy Making: a necessary premise for progress in Romania project was implemented by the Executive Agency for Higher Education, Research, Development and Innovation Funding (UEFISCDI) in the timeframe February 2012 – February 2014, being co-financed by the European Social Fund through the Operational Programme “Administrative Capacity Development”. The project aimed to increase the capacity of public administration for evidence-based policy making in the field of higher education, while focusing on good practices at international level and impact assessment. With the contribution of the national and international experts, the project has generated a number of analysis and studies on the existing higher education public policies (quality assurance, internationalisation, equity, data collection, the Bologna Process, financing of higher education). Based on the results of the project, the book will reunite a number of policy research articles which would tap into the innovative aspects of the project's activities and provide a concise overview of what good practices can be drawn from the empirical research conducted in this project. The book will therefore aim to improve the information on Romanian higher education reforms, as well as on the concrete evidence-based policy proposals which could be transformed into future policy solutions in the Romanian higher education system.